Secretion of a proteolytic anticoagulant by Ancylostoma hookworms (The Rockefeller University Press, 1983)
Hookworms of the genus Ancylostoma secrete an anticoagulant that both inhibits the clotting of human plasma and promotes fibrin clot dissolution. This anticoagulant activity is attributable to a 36,000 dalton proteolytic enzyme. The protease can degrade fibrinogen into five smaller polypeptides that intrinsically have anticoagulating properties, covert plasminogen to a mini-plasminogen-like molecule, and hydrolyze a synthetic peptide substrate with specificity for elastolytic enzymes. It is hypothesized that the parasite uses this enzyme to prevent blood clotting while feeding on villous capillaries.